Material didáctico para el fortalecimiento del aprendizaje en niños y niñas con necesidades educativas especiales - Garzón, Evelyn F. (2017)
In the present work of Grado is designed an educational project which contains applied research for the development of Didactic Material for learning systems in the Center for Comprehensive Municipal Development Renacer located in the Otavalo Canton, Imbabura.